(untitled) (Psicologia USP, 2016)
The need for transmission imposes itself in every generation. However, the issue of the narrative remains and is renewed at every dawn: the borders between genres, the documentary limits, the narrative choices, the narrators, the readers. Such theme might seem odd to Sartre, but not only do I situate it in the heart of his thinking, but also claim its restorative potential as a an instrument of current knowledge. This work seeks to follow the traces of this Sartre, inventor of narrative forms, showing that, since La Nausée, he did not hesitate to put into brackets the genres to propose new forms, more consistent with his experiences and reflections. Alongside the Carnets de la drôle de guerre, Les Mots and L'Idiot de la famille, the effort made in La Nausée shows that, from the fundamental intertwining of life and work, leaps a restorative conception of narrative as mediator of existential transformation.